2018
DOI: 10.17796/1053-4628-42.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Combined Orthodontic and Surgical Treatment in a 8-Years-Old Patient Affected By Severe Obstructive Sleep Apnea: A Case-Report

Abstract: An eight-years-old girl showed a restless sleep with snoring and severe apnea episodes, a mandibular retrognathia, mouth breathing, maxillary transverse discrepancy, mandibular transverse discrepancy, moderate crowding and anterior open-bite. The CBCT showed an anterior collapse of the epiglottis. The treatment consisted in a rapid palatal expansion, an epiglottoplasty and a reduction of the tongue base. Polysomnography revealed that apnea-hypopnea index improved from 21,8 episodes/hr at the baseline to 0,6 ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
17

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 3 publications
0
16
0
17
Order By: Relevance
“…The included studies were categorized into one randomized controlled trial (RCT) [ 27 ], two non-randomized controlled trials (NRCTs) [ 22 , 26 ], two observational case–control studies [ 24 , 25 ] and five case reports [ 18 , 19 , 20 , 21 , 23 ]. The sample sizes ranged from one to 80 subjects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies were categorized into one randomized controlled trial (RCT) [ 27 ], two non-randomized controlled trials (NRCTs) [ 22 , 26 ], two observational case–control studies [ 24 , 25 ] and five case reports [ 18 , 19 , 20 , 21 , 23 ]. The sample sizes ranged from one to 80 subjects.…”
Section: Resultsmentioning
confidence: 99%
“…The mean BMI varied between 15.75 and 22.4, however, only five studies reported the BMI [ 19 , 22 , 23 , 25 , 26 ]. To diagnose and evaluate the severity of OSA, eight studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 27 ] employed PSG and two [ 18 , 26 ] used home sleep studies (HSTs). All study participants received surgery and orthodontic treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the growing recognition of orofacial characteristics as important developmental factors of sleep disorders, as well as their therapeutic implications in some disorders (such as OSAS, snoring and bruxism), dentists are nowadays more conscious of sleep disorders, with a potential role in the diagnostic and therapeutic process [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In childhood an obstructive AHI ≤ 1 episodes/hr is considered to be normal, 1 < AHI ≤ 5 to be mild OSA, 5 < AHI ≤ 10 to be moderate OSA, and an AHI > 10 episodes/hr as severe OSA [7].…”
Section: Introductionmentioning
confidence: 99%